Symmetry plane boundary conditions for cell-centered finite-volume continuum mechanics. (28th November 2022) - Demirdžić, I.; Cardiff, P.
Abstract: A general approach to deriving the symmetry plane boundary conditions for cell-centered finite-volume continuum mechanics is presented. It is equally applicable to scalar, vector, and tensor solution variables. The total contribution of the symmetry plane cell faces to the next-to-symmetry-plane cells is decomposed into implicit and explicit parts, allowing the use of segregated solution algorithms. Using several unstructured mesh test cases, the derived symmetry plane discretizations are shown to be consistent with the discretization on the internal faces.